Löeffler endocarditis due to idiopathic hypereosinophilic syndrome - Laura Benchea; Alexandra Clement; Alina-Elena Nedelcu; Cristian Statescu (Sciendo, 2021)
Hypereosinophilic syndrome encompasses a heterogenous group of non-hematologic and hematologic disorders defined as peripheral blood eosinophilia >1500/mm3 persisting more than 6 months and eosinophilic end organ complications. Löeffler endocarditis (LE) is the most common cardiac manifestation of the hypereosinophilic syndrome (HES) and represents an acute form of primary restrictive cardiomyopathy. We report the case of a 74 years-old woman with symptoms related to congestive heart failure and weight loss. At admission the patient had tachycardia and a grade 2/6 systolic mitral murmur. Laboratory findings revealed eosinophilia, hepatocytolysis syndrome and dyslipidemia. The electrocardiogram (ECG) showed non-specific ST-segment and T wave abnormalities. The echocardiography revealed left ventricular apical thrombus and entrapment of chordae tendineae with restricted motion of mitral leaflets leading to mitral regurgitation. The diagnosis of myocarditis was confirmed by the cardiac magnetic resonance imaging which showed the presence of a left ventricular mass with low signal on steady-state free precession imaging and diffuse circumferential subendocardial late gadolinium enhancement (LGE). When discussing the etiology of the HES the following were taken into consideration: hematologic, reactive or secondary disorders. This case is distinguished by diagnosis in an elderly woman and good response to corticosteroid therapy.